1976
DOI: 10.1139/v76-330
|View full text |Cite
|
Sign up to set email alerts
|

Pyrochlores. X. Madelung energies of pyrochlores and defect fluorites

Abstract: KNOP. Can. 3. Chem. 54, 2316 (1976. Electrostatic (Madelung) lattice energies have been calculated for a wide range of compounds A2B2X6Y with the pyrochlore-type structure. The cases of disorder and partial disorder on the non-metal sites have been examined, as well as the inverse case. where Y is a positive ion. The results of the calculations are compared with those for defect fluorite structure and an attempt is made to relate them to the conditions under which the pyrochlore phase is found. The effect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

1980
1980
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 9 publications
1
10
0
1
Order By: Relevance
“…Again, with variation in x-parameter the shape of polyhedra in pyrochlore also changes. Based on Madelung energy and site potential calculations, it had been found that (3+ , 4+ ) pyrochlores with x E0.36 may also exist but in a highly disordered state [22,23]. Earlier we [24] have shown that for Dy 2 Hf 2 O 7 , the xparameter is 0.348 and it crystallizes as a disordered pyrochlore.…”
Section: Resultsmentioning
confidence: 99%
“…Again, with variation in x-parameter the shape of polyhedra in pyrochlore also changes. Based on Madelung energy and site potential calculations, it had been found that (3+ , 4+ ) pyrochlores with x E0.36 may also exist but in a highly disordered state [22,23]. Earlier we [24] have shown that for Dy 2 Hf 2 O 7 , the xparameter is 0.348 and it crystallizes as a disordered pyrochlore.…”
Section: Resultsmentioning
confidence: 99%
“…20 In natural pyrochlore, molecular water and hydroxyl may be part of the structure so that the general formula becomes: A 1-2 B 2 O 6 (O,OH,F) 0-1 pH 2 O. A number of structural derivatives are possible, such as ''inverse'' pyrochlores, in which the A-site is vacant and monovalent cations occupy the Y-site, ͓ ͔ VI B 2 III X 6 VI M. 55 The M-atom may be displaced from the 8a site to the 32e position, hence the rather unusual flexibility of this structure. Stanek et al 56 have simulated the energetics of vacancy formation using an energy minimization method and a Born-like description of the forces between the ions.…”
Section: Structure and Compositionmentioning
confidence: 99%
“…Combinations of A-site cations and Y-site anions may be removed to produce defect structures described by the formulas VlA2VlB2Ivx6, VIAVlBzmX6,or VIB2nX 6 (Grins 1980;Rotella et al 1982;Chakoumakos and Ewing 1985;Chakoumakos 1984Chakoumakos , 1986. The defect structure known as "inverse" pyrochlore has the formula WByX6VIM and is formed by replacing the Y anion with a large monovalent cation (Barker et al 1976). The range of possible defect structures illustrates why the BzX6 octahedral framework is considered to be the essential structural feature ofpyrochlore (Figure 2).…”
Section: Structure and Chemistry Of Pyrochlorementioning
confidence: 99%